Looks as tho' you have not shared the entire function f(x) = x + (as nothing follows your " + " sign).
Assume that the given function is f(x) = x + c, where c is a constant.
Taking "f(1) = -1", f(x) = x + c becomes f(1) = 1 + c = -1, which means that c must be = to -2:
f(x) = x - 2
When you list those possible answer choices, kindly separate them using commas or semicolons, or type each one on a new, separate line.
Before you do anything else, ensure that you have shared this problem exactly as it was presented in its original form.